2008
DOI: 10.1007/s12210-008-0007-7
|View full text |Cite
|
Sign up to set email alerts
|

Climate reconstructions and monitoring in the Mediterranean Sea: A review on some recently discovered high-resolution marine archives

Abstract: Palaeoclimate records are important tools for understanding climate modifications and contextualizing recent anthropogenic perturbations in climate change relative to natural variability in the Earthclimate system. \ud Moreover, time-series proxy records of the main physical and chemical parameters in marine and continental environments are increasingly used for testing climate models in order to ascertain the reliability of projections for future scenarios in our greenhouse modified Earth. \ud In order to acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Such environmental differences must be cautiously taken into account when investigating and interpreting the skeletal isotope signal of temperate corals. Stable isotope and trace element composition, in combination with U-series and radiocarbon dating of the zooxanthellate coral Cladocora caespitosa, and of the cold-water corals Desmophyllum dianthus, Lophelia pertusa, and Madrepora oculata have been validated as high-resolution paleoenvironmental proxies (Peirano et al, 2004;Silenzi et al, 2005;Cohen et al, 2006;Montagna et al, 2008;López Correa et al, 2010;Trotter et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Such environmental differences must be cautiously taken into account when investigating and interpreting the skeletal isotope signal of temperate corals. Stable isotope and trace element composition, in combination with U-series and radiocarbon dating of the zooxanthellate coral Cladocora caespitosa, and of the cold-water corals Desmophyllum dianthus, Lophelia pertusa, and Madrepora oculata have been validated as high-resolution paleoenvironmental proxies (Peirano et al, 2004;Silenzi et al, 2005;Cohen et al, 2006;Montagna et al, 2008;López Correa et al, 2010;Trotter et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Yet there have been very few sclerochronological studies in the Mediterranean despite a number of possible marine archives including vermetid gastropods (Dendropoma petraeum), non-tropical zooxanthellate corals (Cladocora caespitosa) and coldwater corals (Desmophyllum dianthus, Lophelia pertusa and Madrepora oculata) (Montagna et al, 2008). In perhaps the only Mediterranean example from corals, Peirano et al (2009) constructed a multidecadal growth chronology from a living Cladocora caespitosa.…”
Section: Introductionmentioning
confidence: 99%
“…However, currently, only sparse 14 C data are available for the Mediterranean Sea and those are derived from mol-lusk shells with a limited age range (Siani et al 2000;Reimer and McCormac 2002). Recent studies have revealed that the shallow-water zooxanthellate Mediterranean coral Cladocora caespitosa can serve as a reliable archive for seawater temperature and pH reconstructions (Peirano et al 2004;Silenzi et al 2005;Montagna et al 2007Montagna et al , 2008Trotter et al 2011) and thus is a potentially useful archive for 14 C studies.…”
Section: Introductionmentioning
confidence: 99%